Service Quality Analysis of Primajasa Bus on the Cirebon–Bekasi Route Using the Importance Performance Analysis (IPA) Method - Bima Giri Jati; Nurullah Budisiswanto (Indonesian Journal of Advanced Research, 2026)
Primajasa Bus is an inter-city, inter-province (AKAP) public transport operator whose Cirebon–Bekasi route carries high passenger mobility. This study analyzes the performance and importance levels of Primajasa Bus service attributes, measures their level of conformity, and formulates strategic recommendations for service improvement. A descriptive quantitative approach was used, distributing questionnaires to 100 respondents obtained via Slovin's formula and accidental sampling. The instrument covered 29 attributes across five SERVQUAL dimensions, analyzed with Importance Performance Analysis (IPA). Results show performance scores of 3.77–4.11 (Good) and importance scores of 4.09–4.58 (mostly Very Important), with an overall conformity level of 92.48%, leaving a 7.52% gap. The IPA Cartesian diagram identified seven priority attributes requiring immediate improvement.